2022
DOI: 10.1186/s12933-022-01558-w
|View full text |Cite
|
Sign up to set email alerts
|

Liver function markers predict cardiovascular and renal outcomes in the CANVAS Program

Abstract: Background Raised liver function tests (LFTs) have been correlated with multiple metabolic abnormalities and variably associated with cardiorenal outcomes. We sought to systematically test the relationship between LFT levels within the accepted range and major cardiorenal outcomes in a large clinical trial in type 2 diabetes, and the possible impact of placebo-controlled canagliflozin treatment. Methods We measured serum alanine aminotransferase (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 53 publications
0
9
0
2
Order By: Relevance
“…[34][35][36] This is the case in HF patients: subanalyses of large-scaled randomized controlled studies for HF patients showed that a decline in body weight was associated with a higher risk of all-cause mortality, regardless of the treatment. 17,20,22 The importance of timedependent weight loss in adverse clinical outcomes was supported by a recent retrospective observational study with a large number of HF patients and a prospective observational study carried out in Japan. 18,21,23 In other words, the prediction of prognosis by assessment of body weight at a single point might not necessarily be accurate, as it is unclear whether body weight is in the process of increasing or decreasing compared with the previous time point.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[34][35][36] This is the case in HF patients: subanalyses of large-scaled randomized controlled studies for HF patients showed that a decline in body weight was associated with a higher risk of all-cause mortality, regardless of the treatment. 17,20,22 The importance of timedependent weight loss in adverse clinical outcomes was supported by a recent retrospective observational study with a large number of HF patients and a prospective observational study carried out in Japan. 18,21,23 In other words, the prediction of prognosis by assessment of body weight at a single point might not necessarily be accurate, as it is unclear whether body weight is in the process of increasing or decreasing compared with the previous time point.…”
Section: Discussionmentioning
confidence: 99%
“…17 The importance of time-dependent weight loss in the prediction of prognosis in HF patients was supported by the results of recent studies. [18][19][20][21][22][23] The untoward impact of weight loss on prognosis is at least partly explained by the progression of muscle wasting, but reduction in fat/bone mass, which is usually seen in patients with cachexia, might play a role. Therefore, the presence of time-dependent weight loss potentially has an additive impact on the prediction of prognosis by sarcopenia through detection of patients who entered the cachexic process.…”
Section: Introductionmentioning
confidence: 99%
“…66,67 However, it is still undetermined whether these markers are specific or sensitive in clinical practice; for instance, a recent study conducted through the CANVAS program found that though raised γGT was associated with the risk of HF, ALT levels were independently associated with lower risk. 68…”
Section: Discussionmentioning
confidence: 99%
“…66,67 However, it is still undetermined whether these markers are specific or sensitive in clinical practice; for instance, a recent study conducted through the CANVAS program found that though raised gGT was associated with the risk of HF, ALT levels were independently associated with lower risk. 68 Screening protocols should be equipped to identify certain parameters that would indicate increased CVD risk in NAFLD outside of traditional metabolic markers. Currently, the literature has not reached a consensus on the validity of lipid profiles (i.e., LDL-C levels) or liver enzymes in determining CVD risk within the NAFLD population.…”
Section: Cvd Preventionmentioning
confidence: 99%
“…Moreover, a slower eGFR rate decline for dapagliflozin in DAPA-HF; a reduction of albuminuria and of the risk of kidney function loss, and a slower decline of the eGFR for canagliflozin in CANVAS are reported as safety parameters. In relation to hepatic function, there is a reported reduction of aminotransferases (GPT > GOT), which are secondary to hepatic fat reduction for empagliflozin in EMPA-REG OUTCOME, and of GOT, GPT, and γ-glutamyl transpeptidase (GGT) for canagliflozin in CANVAS, alongside with classical adverse reactions (AR) such as reducing the incidence of hypoglycemia episodes, volume depletion, arrythmias, amputation, urinary tract infections, and all-cause mortality [ 20 , 26 , 27 , 28 , 29 , 30 ]. On the other hand, GLP-1 RAs are reported to reduce 3-point MACE and the rate of myocardial infarction and non-fatal stroke for semaglutide in PIONNER and SUSTAIN, and for liraglutide in LEADER [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%